2007
DOI: 10.1007/s10729-007-9013-z
|View full text |Cite
|
Sign up to set email alerts
|

Predicting joint replacement waiting times

Abstract: Currently, the median waiting time for total hip and knee replacement in Ontario is greater than 6 months. Waiting longer than 6 months is not recommended and may result in lower post-operative benefits. We developed a simulation model to estimate the proportion of patients who would receive surgery within the recommended waiting time for surgery over a 10-year period considering a wide range of demand projections and varying the number of available surgeries. Using an estimate that demand will grow by approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 69 publications
0
10
0
1
Order By: Relevance
“…Increasing the size of the workforce has been discussed and projections in Canada suggest that the annual supply of surgeries must increase by 12% or greater each year to prevent further increases in mean waiting times [34]. Payment reform must also be carefully crafted to incentivize appropriate utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the size of the workforce has been discussed and projections in Canada suggest that the annual supply of surgeries must increase by 12% or greater each year to prevent further increases in mean waiting times [34]. Payment reform must also be carefully crafted to incentivize appropriate utilization.…”
Section: Discussionmentioning
confidence: 99%
“…26 Surgeons in Ontario were grouped into 25 service providing regions: 11 teaching hospitals and 14 groups of community hospitals organized on the basis of Ontario's 14 Local Health Integration Networks. 30 The Ontario Joint Replacement Registry (OJRR) was a clinical registry that collected demographic, medical, surgical, and outcomes information on patients who received TJR in Ontario from 1999 to 2006.…”
Section: Methodsmentioning
confidence: 99%
“…11 One study showed that if 16% increases could be maintained for several years then, within 7 years, 90% of patients would receive surgery within 6 months of their decision to have surgery. 26 However, human resource shortages in orthopedics, 27 anesthesiology, 28 and nursing 29 may prevent this high level of sustained growth.…”
mentioning
confidence: 99%
“…In this journal, the literature review in a recent paper [12] includes an excellent discussion and a list of more than two dozen papers where mathematical models have been used to address issues related to health care resources. In particular, Cipriano et al [12] states that "Queuing theory has been applied to many aspects of heath care including emergency rooms [ It has been suggested that the proper application of a pertinent mathematical model is like a good caricature [13]. In the latter case, the image that results from the use of a small number of well-drawn pen strokes manages to convey the identity of the intended individual.…”
Section: Modelling the Waiting Timesmentioning
confidence: 99%